The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1111/jse.12071
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underlying flower color variation in Asian species ofMeconopsis: A preliminary phylogenetic analysis based on chloroplast DNA and anthocyanin biosynthesis genes

Abstract: The Qinghai-Tibet Plateau (QTP) harbors the highest species diversity of alpine plants in the world, with a spectacular diversity of flower colors. Among these QTP plants, the genus Meconopsis comprises more than 50 species, for which flower color is a key diagnostic character. However, the mechanisms underlying flower color variation have rarely been investigated. In the present study, we used three chloroplast (cp) DNA fragments and two anthocyanin biosynthesis genes (F3H and F3 0 H) for phylogenetic reconst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
(68 reference statements)
0
3
0
Order By: Relevance
“…Although flower colour is changeable in Meconopsis, these two types of colour are usually incompatible and have different pigment bases. Red, violet or blue are due to different derivatives from the anthocyanin biosynthetic pathway, while yellow is due to suppression of anthocyanin (Zhao et al 2014) or dominated by some different compound (Acheson et al 1962, Ono et al 2006. In the natural environment, it is easy to find colour mutations in blue Meconopsis, such as M. horridula and M. grandis, however, the flower colour in yellow Meconopsis, such as M. integrifolia and M. sulphurea is more stable.…”
Section: Identity Of Meconopsis Castaneamentioning
confidence: 99%
“…Although flower colour is changeable in Meconopsis, these two types of colour are usually incompatible and have different pigment bases. Red, violet or blue are due to different derivatives from the anthocyanin biosynthetic pathway, while yellow is due to suppression of anthocyanin (Zhao et al 2014) or dominated by some different compound (Acheson et al 1962, Ono et al 2006. In the natural environment, it is easy to find colour mutations in blue Meconopsis, such as M. horridula and M. grandis, however, the flower colour in yellow Meconopsis, such as M. integrifolia and M. sulphurea is more stable.…”
Section: Identity Of Meconopsis Castaneamentioning
confidence: 99%
“…In plant species, the cp genome is widely used for phylogenetic analyses and molecular marker development to improve phylogenetic resolution at the interspecific level. A great deal of research has been conducted using molecular markers in the study of the phylogeny of the genus Meconopsis [16,17]. Previous studies have complemented previous morphology-based treatments on the phylogenetic relationships of a few Meconopsis species through large-scale sampling and the construction of phylogenetic models using molecular markers [5].…”
Section: Introductionmentioning
confidence: 99%
“…Mao, Li (7) studied eight morphometric traits of cone and seeds in Pinus densata and the parental species and concluded that Pinus densata is more reproductively successful in the natural habitat than the local Pinus tabuliformis and Pinus yunnanensis. Among the three Pinus species, the cross barrier is weak and the fitness differences are determined by local adaptation [8] . These phenotyping assessments are laborious to compare the interspecific variation, involving field sampling, common garden trials, experimental measurement and destructive evaluation methods.…”
Section: Introductionmentioning
confidence: 99%